Pengaruh Struktur Kepemilikan Manajerial, Return on Asset (ROA), dan Financial Leverage Terhadap Manajemen Laba (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021 – 2022) - Utari Maharani Noor; Noor Shodiq Askandar; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted to determine the influence of Managerial Ownership, Return On Asset and Financial Leverage on Earnings Management practices at manufacturing companies listed in the Indonesia Stock Exchange (IDX) with a research period from 2021 to 2022. This research uses quantitative methods. The earnings management practices in this study was measured using the Modified Jones Model. The result of this research shows: (1) the results of this study indicate that managerial ownership, return on assets, and financial leverage have a significant effect on earnings management, (2) managerial ownership has no effect on earnings management, (3) return on assets have no effect on earnings management. Meanwhile, (4) financial leverage has a negative effect on earnings management.Keywords: Earnings management, managerial ownership, return on asset, financial leverage.